Effectiveness of Senior Dance on risk factors for falls in older adults (DanSE): a study protocol for a randomised controlled trial - Franco, Marcia R (BMJ Open, 2016)
INTRODUCTION: Strong evidence shows that exercise is effective to improve fall risk factors among older people. However, older people's participation and adherence to exercise programmes is suboptimal. Type of exercise and apathy are reported to be barriers to exercise participation, suggesting that new effective interventions are needed. The primary aim of this randomised controlled trial is to investigate the effect of Senior Dance plus brief education for falls prevention on balance among people aged 60 years or over, compared with a control group receiving only brief education. METHODS AND ANALYSIS: This single-blind randomised controlled trial will involve 82 community-dwelling older people aged 60 years or over who are cognitively intact. Participants allocated to the intervention group will attend a single educational class on strategies to prevent falls, and will participate in a 12-week, twice-weekly group-based programme of Senior Dance. The Senior Dance consists of different choreographies, which include rhythmic and simple movements with rhythmic folk songs. Participants allocated to the control group will attend the same educational class that intervention group participants will receive, and will be instructed not to take part in any regular exercise programme. The primary outcome will be single-leg stance with eyes closed. Secondary outcomes include: Short Physical Performance Battery, Falls Efficacy Scale, Trail Making Test and the Montreal Cognitive Assessment. Continuous outcomes will be reported using mean (SD) or median (IQR), depending on the distribution of the data. The linear regression approach to analysis of covariance will be used to compare the mean effect between groups. All patients will be included in the analyses following an intention-to-treat approach. ETHICS AND DISSEMINATION: Ethics approval has been granted by the Human Ethics Committee of the São Paulo State University (CAAE 48665215.9.0000.5402). Outcomes will be disseminated through publication in peer-reviewed journals and presentations at conferences. TRIAL REGISTRATION NUMBER: NCT02603523, Pre-results.